Bulletin of the National Research Centre Official International Journal of the National Research Centre of Egypt - Refaat Abdel-Fattah, Yasser; Hamed Shaalan, Ashraf; Ibrahim Shalaby, Said .; Tewfik, Ihab.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Bulletin of the National Research Centre is an open-access, international, multidisciplinary, peer-reviewed journal that publishes research in the fields of health and medical sciences, life sciences, chemistry, physics and engineering. The journal publishes original research, review articles, meta-analysis and medical case studies aiming to communicate advances in each field, focusing on high-quality research, rigorous peer review and rapid dissemination. Bulletin of the National Research Centre is the official international journal of the National Research Centre (NRC) of Egypt. The NRC is the largest Research and Development multidisciplinary centre in Egypt and in the region. The journal covers the following subject areas: Dentistry Pharmaceutical Industries Veterinary Medicine Molecular Biology and Biotechnology Agriculture and Food Industries Chemistry Physics Earth Sciences Ecology, Environmental and Climate Change Engineering and Technology The journal does not consider the following subject areas: Nursing, Mathematics, Humanities and Social Sciences, as well as publishing study protocols are not within the scope of the journal.
Keywords: Molecular biology; Medical genetics; Agriculture; Materials science; Veterinary medicine; Environment; Molecular Biology; Medical Genetics; Agriculture; Materials Science; Veterinary Science; Environmental Sciences